2005
DOI: 10.3758/bf03193228
|View full text |Cite
|
Sign up to set email alerts
|

Advance task preparation reduces task error rate in the cuing task-switching paradigm

Abstract: Advance preparation reduces RT task-switching cost, which is thought to be evidence of preparatory control in the cuing task-switching paradigm. In the present study, we emphasize errors in relation to response speed. In two experiments, we show that (1) task switching increased the rate at which the currently irrelevant task was erroneously executed ("task errors") and (2) advance task preparation reduced the task error rate to that seen in nonswitch trials. The implications of the results to the hypothesis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 71 publications
7
78
3
Order By: Relevance
“…It is important to note that Arbuthnott (2005) showed that conditions in which backward inhibition was small were associated with larger RTTRCEs, suggesting that the RT-TRCE represents incomplete suppression of a competing task set. The second piece of evidence is that the PE-TRCE (Meiran & Daichman, 2005) as well as the RT-TRCE (e.g., Cepeda et al, 2001;Koch & Allport, 2006;Meiran, 2005) increase following a task switch. These results may be interpreted as evidence that the execution of the alternative task set in the previous trial primed its response codes, which resulted in an elevated TRCE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that Arbuthnott (2005) showed that conditions in which backward inhibition was small were associated with larger RTTRCEs, suggesting that the RT-TRCE represents incomplete suppression of a competing task set. The second piece of evidence is that the PE-TRCE (Meiran & Daichman, 2005) as well as the RT-TRCE (e.g., Cepeda et al, 2001;Koch & Allport, 2006;Meiran, 2005) increase following a task switch. These results may be interpreted as evidence that the execution of the alternative task set in the previous trial primed its response codes, which resulted in an elevated TRCE.…”
Section: Methodsmentioning
confidence: 99%
“…An important consideration is that participants could respond correctly in congruent trials even when applying the wrong task rule (Meiran & Daichman, 2005). To ensure that they rarely did so, we used a high proportion of incongruent trials (.75) in all the experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, every possible response, and likewise every possible error, was mapped onto a different effector. This allows inferring from the subject's responses which type of error was made (Meiran and Daichman, 2005). A response error corresponds to a response with the correct hand but with the wrong finger of that hand.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to Meiran and Daichman (2005), we used univalent stimulus-response mappings. This means that we mapped every possible response to one effector.…”
Section: Methodsmentioning
confidence: 99%